KAJIAN HUKUM KEKUATAN AKTA RISALAH LELANG YANG DIBUAT OLEH NOTARIS SEBAGAI PEJABAT LELANG KELAS II DALAM PERKARA PERDATA - DWI NURUL AMALIA (PREMISE LAW JURNAL, 2016)
An auction sale is a legal document report from the process of auction execution arranged based on the Ministry of finance Decree No. 106/PMK.06/2013 about the changes of the Ministry Finance Decree No. 93/PMK.06/2010 about the changes of auction execution. One of the characteristics auction sale certificate is made by the an auction official appointed by the Minister authorized to lead the auction process. The research is related to a notary as a public official who can undertake dual positions as an auction official of class II. The problems of the research are how the legal regulation of a notary’s authority is an Auction of official Class II to lead the Auction process, and how the legal power of the Auction certificate is to prove made by the Notary as the Auction Official Class II in civil case. Keywords: Auction Sale Certificate, Notary, Auction Official Class II